The effect of early postnatal exposure to pyrethroid (deltamethrin) and pyrethroid-based mosquito repellent on the cerebellum of rats - Asari, Mohd Asnizam; Ismail, Zul lzhar Mohd; Mansor, Othman (Pusat Pengajian Sains Kesihatan Universiti Sains Malaysia, 2009)
Deltamethrin is a widely used type II pyrethroid-based insecticide. Studies indicated that neonatal exposure to deltamethrin even at relatively low dose resulted in behavioral and neurological changes. In the present study, the effect of early neonatal exposure to low dose deltamethrin on the histogenesis of the cerebellar cortex was investigated. Sprague Dawley male pups were exposed to deltamethrin in a dose of 1 mg/kg/day via intraperitoneal injection from 2"d to 5lh postnatal day and sacrificed on postnatal day 6, 14 and 21. The cerebellum was removed, processed, embedded with paraffin wax and serially sectioned. Cerebelar tissue sections were stained with Harris hematoxylin and eosin and anti-synaptophysin immunohistochemistry. The thickness of the different layers of the cerebellar cortex and the optical density of the molecular layer were measured using Image Proplus software. The results showed no differences in the measured thickness of the external granular, molecular and internal granular layers between the deltamethrin-treated and the control animals in all age groups studied. There were significant upregulation of the synaptophysin immunoreactivity in the molecular layer when examined at postnatal day 6, but not at postnatal day 14 and 21. In conclusion, the present study showed that neonatal administration of the deltamethrin at the current dosage did not significantly affect the morphogenesis of the cerebellar cortex.